PENGARUH KOMITMEN ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi pada Karyawan Tidak Tetap dan Kontrak CV. Inspira) - Galih Sabiila Rosyad; Rini Nugraheni (Faculty of Economics and Business | Universitas Diponegoro, 2019)
In the current era, many companies that are starting to stand up either large scale or small scale cause competition among companies that arises requiring to follow trends in carrying out company activities, especially human resource development activities. Organizational commitment is considered important for the sustainability of the company, where employees can devote ideas, ideas, thoughts and energy to achieve the work expected by the company. In addition, if employees have motivation in doing their jobs, it is expected that employees are able to obtain good work results. Therefore there is a need for testing related to organizational commitment and motivation on the performance of employee case studies on temporary employees and contracts on CV. Inspira.Population in this study were 80 employees who are divided by non-permanent employees and contracts in CV. Inspira. The sampling technique in this study used quota sampling. The questionnaire is used as a research instrument for data retrieval. This type of research is quantitative descriptive while the data obtained are analyzed through multiple regression analysis and for the analysis tool used in this study, namely SPSS 20.The results showed that organizational commitment had a significant effect on employee performance, both for temporary employees and contract employees. Work motivation as another variable also has a significant effect on the performance of non-permanent employees, but contract employees show that motivation does not significantly influence employee performance. In addition, there are differences between organizational commitment, motivation and performance between temporary employees and contract employees. It is recommended for companies to pay more attention or review related incentives and bonuses given to employees, especially in this study employees who are status as contract employees so as to improve the performance of employees in the company.